[PP.02.07] SIMPLIFICATION OF ANTIHYPERTENSIVE THERAPY IMPROVES BLOOD PRESSURE CONTROL IN RESISTANT ARTERIAL HYPERTENSION. (September 2017) - Vaclavik, J.; Flasik, J.; Jarkovsky, J.; Benesova, K.; Kocianova, E.; Kamasova, M.; Vaclavik, T.
Abstract : Objective: Partial or total non-adherence to antihypertensive medications is a frequent cause of inadequate blood pressure (BP) control. Fixed combinations were shown to improve medication adherence and BP control, but their effect in resistant hypertension is not known. The aim of our study was to assess the effects of simplification of the antihypertensive treatment using fixed combinations in patients with resistant arterial hypertension. Design and method: We analyzed medical records of patients with resistant arterial hypertension, who had antihypertensive medication adjusted and simplified using fixed combinations during an outpatient visit at our department between November 2009 and June 2015. Office blood pressure and antihypertensive medications were recorded and compared between baseline and the next outpatient clinical visit. Standard descriptive statistical methods were applied, statistical significance of BP and medication changes was calculated using Wilcoxon Rank test. Results: We enrolled 194 patients of mean age 60 years, 63% were men. Mean baseline office BP was 153.7/87.5 mmHg and patients were using mean 4.8 different antihypertensive drug classes, representing mean 5.2 antihypertensive tablets used daily. Effect of the simplification of medication was assessed on next clinical visit on average 12 weeks later. Number of antihypertensive drug classes was reduced by 0.4 to 4.4, and the number of daily used antihypertensive tablets was reduced by 1.9 to 3.3 (P < 0.001 for both). Office blood pressure at the next clinical visit decreased by a mean 19.8/9.9 mmHg to 133.9/77.6 mmHg (P < 0.001 for both). Conclusions: Simplification of medication using fixed combinations markedly improved BP control in patients with resistant hypertension while significantly decreasing their medication burden.